Power-law models of totally anisotropic scattering - Tuntsov, A.; Bignall, Hayley; Walker, M. (Oxford University Press, 2013)
The interstellar scattering responsible for pulsar parabolic arcs, and for intraday variability of compact radio quasars, is highly anisotropic in some cases. We numerically simulate these observed phenomena using totally anisotropic, power-law models for the electron density fluctuations which cause the scattering. By comparing our results to the scattered image of PSR B0834+06 and, independently, to dual-frequency light curves of the quasar PKS 1257−326, we constrain the nature of the scattering media on these lines of sight. We find that models with spectral indices slightly below β = 3, including the one-dimensional Kolmogorov model, are broadly consistent with both data sets. We confirm that a single physical model suffices for both sources, with the scattering medium simply being more distant in the case of B0834+06. This reinforces the idea that intraday variability and parabolic arcs have a common cause in a type of interstellar structure which, though obscure, is commonplace. However, the implied gas pressure fluctuations are large compared to typical interstellar pressures, and the magnetic stresses are much larger still. Thus while these scattering media may be commonplace, their underlying dynamics appear quite extraordinary.